2016
DOI: 10.1037/xhp0000228
|View full text |Cite
|
Sign up to set email alerts
|

Remembering faces and scenes: The mixed-category advantage in visual working memory.

Abstract: We examined the mixed-category memory advantage for faces and scenes to determine how domain-specific cortical resources constrain visual working memory. Consistent with previous findings, visual working memory for a display of 2 faces and 2 scenes was better than that for a display of 4 faces or 4 scenes. This pattern was unaffected by manipulations of encoding duration. However, the mixed-category advantage was carried solely by faces: Memory for scenes was not better when scenes were encoded with faces rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 46 publications
7
40
4
Order By: Relevance
“…On the one hand, we found the mixed-category benefit for faces was stronger than that for scenes. This result was consistent with the research by Jiang, Remington, et al ( 2016 ) and supported the category-specific cortical resources theory. On the other hand, we also found the similarity advantage for scenes was stronger than for faces.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the one hand, we found the mixed-category benefit for faces was stronger than that for scenes. This result was consistent with the research by Jiang, Remington, et al ( 2016 ) and supported the category-specific cortical resources theory. On the other hand, we also found the similarity advantage for scenes was stronger than for faces.…”
Section: Discussionsupporting
confidence: 93%
“…al. ( 2016 ), which increased the similarity among scenes by employing scenes drawn from the same subcategory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen et al (2014) showed that VWM is enhanced by increased cortical resources, and this facilitation can take place either during early perceptual processing or during later stages, where memory is stored and retrieved. If increased cortical resources facilitate perceptual processing of multiple stimuli under brief encoding duration, this memory facilitation should decrease when ample time is given to encode (Eng et al, 2005;Jiang et al, 2016). Thus, to test whether the residual memory advantage for fearful faces is attributed to increased cortical resources that reduce interference among multiple faces, rather than presenting encoding displays for a limited duration, future studies should provide participants with sufficient time to encode in a self-paced condition to test whether the memory advantage disappears.…”
Section: Still a Residual Memory Advantage For Fearful Facial Expressmentioning
confidence: 99%
“…By comparing VWM performance for faces encoded in emotionally homogeneous and heterogeneous displays, it is possible to observe how memory for faces with a particular facial expression may change depending on the coinciding expressions and their allotted attentional resource. If the distribution of attentional resource plays a critical role in VWM enhancement, the asymmetric allocation of limited resource would result in a memory trade-off between items that are prioritized and those that are not when the displayed items are heterogeneous rather than homogeneous (Jiang, Remington, Asaad, Lee, & Mikkalson, 2016). On this basis, if negative expressions receive a greater portion of attentional resource during perceptual encoding, only memory for faces with negative expressions would increase when they are presented with neutral faces compared to when they are presented with other negative faces.…”
Section: Introductionmentioning
confidence: 99%